Cationic liposomes mediated transdermal delivery of meloxicam and ketoprofen: Optimization of the composition, in vitro and in vivo assessment of efficiency - Kuznetsova, Darya A.; Vasileva, Leysan A.; Gaynanova, Gulnara A.; Vasilieva, Elmira A.; Lenina, Oksana A.; Nizameev, Irek R.; Kadirov, Marsil K.; Petrov, Konstantin A.; Zakharova, Lucia Ya; Sinyashin, Oleg G. (International journal of pharmaceutics, 2021)
[Display omitted] •Stable liposomes non-covalently modified with pyrrolidinium amphiphiles were obtained.•Fabricated liposomes have been used for encapsulation of meloxicam and ketoprofen.•Liposomal ketoprofen and meloxicam were tested for transdermal delivery in vitro.•In vivo assay approved liposomal ketoprofen as effective inflammation reducing agent. New liposomes modified with pyrrolidinium surfactants containing a hydroxyethyl fragment (CnPB, n = 12, 14, 16) were prepared for transdermal delivery of non-steroidal anti-inflammatory drugs. In order to obtain the optimal composition, the surfactant/lipid molar ratio (0.02/1; 0.029/1; 0.04/1) and the amphiphile hydrocarbon tail length were varied. Rhodamine B was loaded in all formulations, while meloxicam and ketoprofen in selected ones. For liposomes studied the hydrodynamic diameter was in the range of 80–130 nm, the zeta potential ranged from +35 to +50 mV, EE was 75–99%. Liposome modification leads to a prolonged release of the rhodamine B (up to 10–12 h) and faster release of non-steroidal drugs (up to 7–8 h) in vitro. The ability to cross the skin barrier using Franz cells was investigated for liposomal meloxicam and ketoprofen. The total amount of meloxicam and ketoprofen passed through the Strat-M® membranes during 51 h was 51–114 μg/cm2 and 87–105 μg/cm2 respectively. The evaluation of transdermal diffusion ex vivo showed that total amount of liposomal ketoprofen passed through the skin during 51 h was 140–162 μg/cm2. Liposomes modified with C16PB were found as the most effective inflammation reducing formulation in the carrageenan edema model of rat paw.